THE USE OF SHORT ENGLISH MOVIES WITH ENGLISH SUBTITLED ON IMPROVING STUDENTS’ READING COMPREHENSION OF ELEVENTH GRADE - Nur Laely Novianti; Agus Mulyana; Syifa Fadhilah Hamid (PRIMACY Journal of English Education and Literacy, 2024)
Reading in English provides learners with the opportunity to develop their vocabulary, improve their comprehension skills. In this research, the writer wants to know the significant effect on students’ reading comprehension with using short English movies with English subtitled. This research used a quantitative method with quasi- experimental design. The population in this research were eleventh grade students from SMK Gemilang Modernland. During data collection, the writer gave a pre-test and post-test which included a total of five essay questions. The writer used IBM SPSS version 25 to analyze the data. The results of the research showed that the data were not normally distributed, and the data were homogeneous. Hypotheses testing used non-parametric statistics, the Wilcoxon Signed Rank Test which indicated that, Ha is accepted, and Ho is rejected. It can be concluded that there is a significant effect of using short English movies with English subtitled in improving students’ reading comprehension at eleventh grade students of SMK Gemilang Modernland in the Academic Year 2023/2024.